Lembar Kerja Peserta Didik Materi Aritmatika Sosial dengan Model Pengembangan Thiagarajan - Isnaini Nur Azizah (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2017)
This research aims to produce comic-based LKPD comic products on the subject of social arithmetic and how to develop comic-based LKPD to be effective. This research uses research method of development of Thiagarajan-4D model, which consists of 4 stages, namely definition, design, development and dissemination. This study begins from a preliminary study in the form of needs analysis consisting of learner analysis, material analysis and task analysis. Preliminary study results indicate the need for the development of comic-based LKPD on the subject of social arithmetic. The development of worksheet based comic begins with arranging worksheet design and all components based on guidance of worksheet preparation in the form of draft 1. The draft 1 has been compiled and then validated by expert to produce draft 2. The validation result indicates that worksheet has fulfilled the content and design feasibility standard. The draft 1 is then refined to produce draft 2 and tested to several learners called a limited trial. The results of a limited trial show that worksheet is included in either category.